Bumepamine, a brain-permeant benzylamine derivative of bumetanide, does not inhibit NKCC1 but is more potent to enhance phenobarbital's anti-seizure efficacy. (December 2018) - Brandt, Claudia; Seja, Patricia; Töllner, Kathrin; Römermann, Kerstin; Hampel, Philip; Kalesse, Markus; Kipper, Andi; Feit, Peter W.; Lykke, Kasper; Toft-Bertelsen, Trine Lisberg; Paavilainen, Pauliina; Spoljaric, Inkeri; et al.
Abstract: Based on the potential role of Na-K-Cl cotransporters (NKCCs) in epileptic seizures, the loop diuretic bumetanide, which blocks the NKCC1 isoforms NKCC1 and NKCC2, has been tested as an adjunct with phenobarbital to suppress seizures. However, because of its physicochemical properties, bumetanide only poorly penetrates through the blood-brain barrier. Thus, concentrations needed to inhibit NKCC1 in hippocampal and neocortical neurons are not reached when using doses (0.1–0.5 mg/kg) in the range of those approved for use as a diuretic in humans. This prompted us to search for a bumetanide derivative that more easily penetrates into the brain. Here we show that bumepamine, a lipophilic benzylamine derivative of bumetanide, exhibits much higher brain penetration than bumetanide and is more potent than the parent drug to potentiate phenobarbital's anticonvulsant effect in two rodent models of chronic difficult-to-treat epilepsy, amygdala kindling in rats and the pilocarpine model in mice. However, bumepamine suppressed NKCC1-dependent giant depolarizing potentials (GDPs) in neonatal rat hippocampal slices much less effectively than bumetanide and did not inhibit GABA-induced Ca 2+ transients in the slices, indicating that bumepamine does not inhibit NKCC1. This was substantiated by an oocyte assay, in which bumepamine did not block NKCC1a and NKCC1b after either extra- or intracellular application, whereas bumetanide potently blocked both variants of NKCC1. Experiments with equilibrium dialysis showed high unspecific tissue binding of bumetanide in the brain, which, in addition to its poor brain penetration, further reduces functionally relevant brain concentrations of this drug. These data show that CNS effects of bumetanide previously thought to be mediated by NKCC1 inhibition can also be achieved by a close derivative that does not share this mechanism. Bumepamine has several advantages over bumetanide for CNS targeting, including lower diuretic potency, much higher brain permeability, and higher efficacy to potentiate the anti-seizure effect of phenobarbital. Highlights: The NKCC1 inhibitor bumetanide has been proposed to potentiate phenobarbital's anti-seizure activity. However, bumetanide hardly reaches brain levels sufficient to inhibit neuronal NKCC1. The brain-permeant bumetanide derivative, bumepamine, is more potent to potentiate phenobarbital. However, even at high concentrations, bumepamine does not inhibit NKCC1. Thus, CNS effects of bumetanide can also be achieved by a close derivative that does not inhibit NKCC1.